Development of Meaningful and Fun Learning with a Gamification-Based GI Model for Primary School Students - Angelikus Nama Koten; Gaudensius Jati Lamauran Koten; Thomas Kemil Masi; Trio Erawati Siregar (Jurnal Penelitian Pendidikan IPA, 2025)
Meaningful learning is when students are actively and constructively involved and the role of students is dominant in every series of learning. Therefore, in order for students to truly carry out their role as the center of learning, learning must be fun and not boring. This study developed a learning design with an integration between the Group Investigation (GI) model and the Gamification approach. The purpose of the study was to produce a learning design (teaching module) on the material of grade V Elementary School in the subject of science with the topic "Human Blood Circulation" that is valid, interesting and practical to be used in creating meaningful and enjoyable learning for students. The learning device development model in this study is the 4-D model with the stages of Define, Design, Develop, and Disseminate. For the practicality and effectiveness of the developed learning design, it was tested in the learning process by 5 elementary school teachers in Kupang City. Departing from the process and stages of development carried out, it can be concluded that the learning device developed by implementing the GI model based on gamification is valid, interesting, and practical and ready to be used in creating a meaningful and enjoyable learning process for students.